me ajudem amigos 1) (1 + 2i) . (2 - i) =
Soluções para a tarefa
Respondido por
1
Explicação passo-a-passo:
(1 + 2i).(2 - i)
= 2 - i + 4i - 2i²
= 2 + 3i - 2.(-1)
= 2 + 3i + 2
= 2 + 2 + 3i
= 4 + 3i
Respondido por
0
Olá!!
Resolução!!
(1 + 2i).(2 - i) = 2 - i + 4i - 2i²
= 2 + 3i - 2.(-1)
= 2 + 3i + 2
= 4 + 3i
Resposta: 4 + 3i
★Espero ter ajudado!!
Perguntas interessantes
Administração,
9 meses atrás
Geografia,
9 meses atrás
Matemática,
9 meses atrás
Português,
1 ano atrás
Biologia,
1 ano atrás
Geografia,
1 ano atrás